Mass supervision: probation, parole, and the illusion of safety and freedom - Schiraldi, Vincent (The New Press, 2023)
"The first comprehensive history of probation and parole-and a provocative and compelling argument for abolishing both-from the former Probation Commissioner of New York City"--